(untitled) (Revista Linhas, 2007)
This article presents some theoretical and practical factors related to strategies of inclusive education. The research indicated the possibility for the integration of children with cognitive disabilities into regular schools, in order to eliminate their segregation in special schools. The most important method for this process of integration is team-work and collaboration between institutions. Key-Words: Cognitive disabilities. Strategies. Inclusive education. Regular schools. Segregation. Este artigo apresenta alguns fatores teóricos e práticos relacionados às estratégias da educação inclusiva. A pesquisa indicou a possibilidade de integração de crianças com deficiências cognitivas em escolas regulares, de modo a evitar sua segregação em escolas especiais. O método mais importante nesse processo de integração é o trabalho em equipe e a colaboração entre instituições. Palavras-chave: Deficiências cognitivas. Estratégias. Educação inclusiva. Escolas regulares. Segregação